2019
DOI: 10.1177/1475921719872939
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect modeling in structural health monitoring of concrete dams using kernel extreme learning machines

Abstract: Statistical models have been used for dam health monitoring for many years and have achieved some successful applications. In the statistical model, dam structural response is related to external environmental factors such as reservoir water level, temperature, and irreversible time deformation. For concrete dams, the structural response is affected greatly by the ambient temperature. Therefore, in order to establish a more reliable dam health monitoring model, the temperature effect and modeling method should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 38 publications
(100 reference statements)
2
38
0
Order By: Relevance
“…Ranković, Grujović, Divac, and Milivojević (2014) integrated previously measured displacements into a set of factors to form an SVR-based nonlinear autoregressive model with exogenous inputs. Kang, Li, and Dai (2019) and Kang, Liu, and Li (2019b) simulated the temperature effect by analyzing long-term actual ambient air temperature. It was found that, by explicitly modeling air temperature effect, the prediction error was significantly reduced.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Ranković, Grujović, Divac, and Milivojević (2014) integrated previously measured displacements into a set of factors to form an SVR-based nonlinear autoregressive model with exogenous inputs. Kang, Li, and Dai (2019) and Kang, Liu, and Li (2019b) simulated the temperature effect by analyzing long-term actual ambient air temperature. It was found that, by explicitly modeling air temperature effect, the prediction error was significantly reduced.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…where a 0 , …, a 11 are fitting coefficients, h is the upstream water depth [34,35] or water level [24], s = 2πd/365.25, 2π/365.25 is a constant related to annual frequency, d is the number of days observed in a year, and t is the number of days since the beginning of the analysis.…”
Section: Displacement Prediction Modelmentioning
confidence: 99%
“…To better interpret the nonlinear thermal displacement in statistical models, many advanced HST and HTT models for thermal effect simulation have been proposed [9,17,18,[20][21][22][23]. In our recent study [24], a mathematical model based on kernel-extreme learning machines (KELM) algorithm [25,26] with long-term daily air temperature monitoring data series was proposed for displacement prediction modeling of concrete gravity dams. Compared to the traditional HST model based on the MLR method, the performance of the prediction model has been significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…The kernel extreme learning has shown speed in accuracy and performance. The simulation was also undertaken in real dam concrete gravity and the results are feasible to application [9].…”
Section: Machine Learning Applications In Recent Dam Water Researchmentioning
confidence: 99%